Current Standards and Practices Within the Therapy Dog Industry: Results of a Representative Survey of United States Therapy Dog Organizations - Serpell, James A.; Kruger, Katherine A.; Freeman, Lisa M.; Griffin, James A.; Ng, Zenithson Y. (Frontiers in Veterinary Science, 2020)
Organizations that deliver animal-assisted interventions (AAIs), as well as those that train, evaluate, and register therapy dogs, have proliferated in recent decades in the United States (U.S.). Each of these organizations has its own policies and procedures for screening, evaluating, and instructing dogs and their owners/handlers, but little is currently known about the range of different practices that exist nationwide. The aim of this project was to survey a representative, national sample of U.S. therapy dog organizations to investigate commonalities and differences in the types of practices in current use and to compare these to recommendations in existing published guidelines. The findings suggest the need for further research, and highlight a number of areas relating to dog welfare, human safety, and infection control in which many organizations were inconsistent in their adherence to existing guidelines. Of particular concern with regard to animal welfare was the finding that approximately half of the organizations surveyed imposed no time limit on the length of visits. Also, given the potential for zoonotic disease transmission, the finding that only a small minority of organizations prohibit the feeding of raw meat diets and treats to visiting dogs is concerning. This information will help to raise awareness among facilities with therapy animal programs and assist in the development of future best practices within the therapy dog industry.